VD_FINDINFO HC / 2010 / 600 vom 31. August 2010 - VD Tribunal cantonal (2010)
FORMALISME EXCESSIF, AVANCE DE FRAIS, DÉFAUTCONTUMACE | 135 CPC, 444 al. 1 ch. 3 CPC, 90 al. 3 CPC, 29 al. 1 Cst., 13 al. 1 TFJC, 13 al. 2 TFJC, 13 TFJC